EVALUASI WAKTU TUNGGU PELAYANAN RESEP OBAT PASIEN RAWAT JALAN DI PUSKESMAS PEDAN KABUPATEN KLATEN - setiyanto, Riyan; Putri, Vania Santika; Utami, Agustina Sri (Jurnal Farmasindo: Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Pharmaceutical services at community health center are the final stage of the servive process which is a service for taking medicines with the provision that the waiting time for prescription services for compounded medicines ≤60 minutes and prescriptions for non-compounded medicines ≤30 minutes. Waiting time prescription services has an important role in health services, because service time is factor for measuring the effectiveness of an organization which consists of accuracy and speed of time. This study aims to determine the average waiting time for prescription drug services at Pedan Health Center, Klaten Regency. This type of research is non-experimental quantitative descriptive with a sampling method, namely incidental sampling carried out by chance using a form for waiting time for prescription drug services. The number of samples taken was 100 prescription sheets consisting of 50 compouned drug prescriptions and 50 non-compounded drug prescriptions. Evaluation of research data was carried out by comparing the result of the average waiting time at the community health center with the applicable laws and regulations. The results of research at the Pedan Community Health Center showed an average waiting time for services for compounded drug prescriptions of 19,92 minutes and non- compounded prescriptions of 11,88 minutes. This show that the average waiting time for prescriptions drug services at the Pedan Community Health Center has met the Minimum Service Standards (SPM) in the healt sector in Minister of Healt Regulation No 4 of 2019, namely compounded prescriptions services ≤60 minutes and non-compounded prescriptions ≤30 minutes. Factors that can influence the length of waiting time for prescription drug services are human resource factors (pharmacy pesonel), equipment used, material factors and method factors. Keywords: Medicine, Community health center, Services, Prescription, Waiting time